Revision of the genus Nesosteropus Ganglbauer, 1891 (Coleoptera: Carabidae, Pterostichini) - Giachino, Pier Mauro; Allegro, Gianni; Picciau, Luca; Vailati, Dante (Fragmenta entomologica, 2025)
The genus Nesosteropus Ganglbauer, 1891, which is part of the Speluncarius + Tapinopterus complex, is taxonomically reviewed and four new species from Greece are described: Nesosteropus euboicus n. sp., N. confusus n. sp., N. montisochae n. sp. and N. breiti n. sp. Nesosteropus diadochos (Lutschnik, 1915) has to be considered the type species of the genus.